Welfare state adjustment to new social risks in the post-crisis scenario. A review with focus on the social investment perspective - Thomas Leoni (WWWforEurope, 2015)
The European welfare states have undergone a significant amount of change over the last decades. In light of the unresolved tensions resulting from changed macroeconomic conditions, the emergence of new social risks as well as from the consequences of the Great Recession and its aftershocks, more adjustments are needed. The present policy paper investigates the current outlook on welfare state change, retracing the socio-economic drivers of this change and the salient steps that were undertaken to reform welfare states in the last decades. Since the outbreak of the crisis, calls to adopt a social investment perspective on welfare state reform intensified, both in the academic field and at the EU policy-level. Ample space is therefore devoted to the discussion of this perspective, its conceptual background, ambiguities and applications. For a number of reasons, social investment seems the most appropriate approach to frame the objectives that contemporary welfare states have to pursue and to devise a consistent set of policies. The objections which have been moved against the social investment perspective have however to be taken seriously. This concerns the conceptual framework on which the social investment idea is based, but in particular its policy implementation and the relationship between its three central pillars: activation, human capital development and social inclusion.
Keywords: H5; I3; 330; Challenges for welfare system; Comprehensive social system; Demographic change; EU integration; European governance; Gender; Labour markets; Post-industrialisation; Welfare reform; Welfare state